2017
DOI: 10.1039/c7ra02402a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photocatalytic dye degradation over Er-doped BiOBr hollow microspheres wrapped with graphene nanosheets: enhanced solar energy harvesting and charge separation

Abstract: In this work, Er-doped BiOBr hollow microspheres wrapped with graphene nanosheets, which acted as a photocatalyst with excellent photocatalytic activity and stability, have been successfully synthesized through a simple two-step hydrothermal method. The related properties of the as-prepared photocatalyst were analyzed and a possible reaction mechanism was proposed. Incorporating the rareearth element Er into the BiOBr crystal lattice can greatly expand the optical window, maybe owing to the reduced energy band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…Hence, these are now considered as one of the promising materials in environmental cleaning. Other successful tuning of BiOBr's properties has also been reported [41,53,[57][58][59][60][61]. In particular, TiO 2 /MWCNT composite was able to degrade oxalic acid and phenol [62].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Hence, these are now considered as one of the promising materials in environmental cleaning. Other successful tuning of BiOBr's properties has also been reported [41,53,[57][58][59][60][61]. In particular, TiO 2 /MWCNT composite was able to degrade oxalic acid and phenol [62].…”
Section: Introductionmentioning
confidence: 68%
“…Two major challenges for many photocatalysts, including BiOBr, are the prevention of recombination of electrons and holes [52], and efficient harvesting of solar energy [53], both of which drastically affect the photocatalytic activity. One way to remediate these problems is by doping or preparing composites materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, BiOBr shows low photocatalytic performance with visible light, thus limiting its use for practical applications in environmental remediation. Researchers have reported that the BiOBr performance can be improved by metal ion doping, noble metal deposition and developing semiconductor composites . These approaches have helped in tailoring band‐edge position and enabling charge separation and ultimately increasing the photoactivity of BiOBr.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has also been reported that Er-doped BiOBr–graphene hollow microspheres exhibited a major improvement in photocatalytic activity for the degradation of RhB under simulated sunlight irradiation, which may be due to the strong synergistic effect between charge separation and solar energy harvesting. 202 In summary, compared with other layered materials, graphene is much more appealing to exactly regulate the behaviors of photogenerated electrons and holes in bismuth oxyhalide-based composite photocatalysis systems, largely due to its flexible atom-thin 2D nature, unique electronic properties and excellent absorptivity, which are promising candidates in photocatalysis. 203 …”
Section: Techniques For Enhancing the Photocatalytic Activity Of Bism...mentioning
confidence: 99%